The Routledge handbook of Mormonism and gender
1 online resource.
Keywords: "The Routledge Handbook of Mormonism and Gender is an outstanding reference source to this engaging and controversial subject area. Since its founding in 1830, the Church of Jesus Christ of Latter-day Saints has engaged gender in surprising ways. LDS practice of polygamy in the nineteenth century both fuelled rhetoric of patriarchal rule as well as gave polygamous wives greater autonomy than their monogamous peers. The tensions over women's autonomy continued after polygamy was abandoned and defined much of the twentieth century. In the 1970s, 1990s, and 2010s, Mormon feminists came into direct confrontation with the male Mormon hierarchy. These public clashes produced some reforms, but fell short of accomplishing full equality. LGBT Mormons have a similar history. These confrontations are part of the larger story of how Mormonism has positioned itself in the context of changing gender norms in a global context. Comprising over forty chapters by a team of international contributors the Handbook is divided into four parts: Methodological Issues, Historical Approaches, Social Scientific Approaches, Theological Approaches. Within these sections central issues, debates and problems are examined, including: agency, feminism, sexuality and sexual ethics, masculinity, queer studies, plural marriage, homosexuality, race, scripture; gender and the priesthood, the family, sexual violence, and identity. The Routledge Handbook of Mormonism and Gender is essential reading for students and researchers in religious studies, gender studies and women's studies. The Handbook will also be very useful for those in related fields, such as cultural studies, politics, anthropology and sociology"--